Tlingit halibut hooks : an analysis of the visual symbols of a rite of passage. Anthropological papers of the AMNH - Jonaitis, Aldona, 1948- (New York : American Museum of Natural History, 1981)
48 p. : ill. 26 cm. Bibliography: p. 46-48.